A Pilot Study of Nicotine Replacement Therapy Sampling and Selection to Increase Medication Adherence in Low-Income Smokers. Issue 9 (23rd March 2021) - Cropsey, Karen L; Wolford-Clevenger, Caitlin; Sisson, Michelle L; Chichester, Keith R; Hugley, Mickeah; Azuero, Andres; Businelle, Michael S; Hendricks, Peter S; Shelton, Richard C; Carpenter, Matthew J
Abstract: Introduction: Adherence to smoking cessation medications remains suboptimal, particularly among low-income smokers. Guided, experiential sampling of nicotine replacement therapies (NRTs) may increase NRT adherence and smoking cessation over gold standard counseling plus NRT. The present pilot study aimed to examine feasibility, acceptability, and preliminary efficacy of a novel experiential intervention. Aims and Methods: This pilot randomized controlled trial ( N = 83) compared gold standard smoking cessation treatment (four weekly sessions of behavioral counseling followed by self-selected combination NRT in week 5) to a novel experiential approach (ie, In Vivo; four weekly sessions of sampling each short form of NRT-gum, lozenge, inhaler, nasal spray-in-session while wearing the nicotine patch followed by NRT selection in week 5). Both groups received 8 weeks of nicotine patch plus their selected additional short form NRT for smoking cessation followed by a 1-month assessment. Results: Screening and enrollment rates supported feasibility. In Vivo was comparable in acceptability with the gold standard of care intervention; however, there was greater attrition in the In Vivo group compared with the gold standard of care group. Results suggested higher medication adherence and improvements in smoking behavior in the In Vivo intervention; with generally small-to-medium effect sizes. Conclusions: This experiential approach to sampling NRT is feasible and acceptable to low-income people who smoke. This intervention may increase adherence and reduce harmful smoking behavior but needs to be tested on a larger scale. Implications: Medication adherence remains a significant impediment to the successful smoking cessation. The results of this study suggest that guided sampling of NRT products improves adherence among low-income smokers. Additionally, this approach yielded greater improvements in smoking behavior compared with gold standard smoking cessation treatment. This intervention shows promise as a feasible smoking cessation treatment for low-income smokers.